Leucaena–Derived Biochar for Biodiesel Production - Jutaporn Chanathaworn; Chokchai Yatongchai; Saluma Samanman (Universitas Jenderal Soedirman, 2022)
Giant leucaena wood was utilized to prepare heterogeneous catalysts through a fast pyrolysis method and chemical activation for transesterification. The obtained catalysts were investigated using SEM, CHNS/O analyzer, XRF and XRD. The influence of the concentration of KOH (3-9 M), catalyst amount (0.25-2.0 g), methanol to oil ratio (4:1-10:1), and reaction time (30-75 min) on FAME yield was also studied on transesterification reaction carried out at 60ºC under a 750 rpm stirring speed. The experiment results demonstrate that chemical activation was required to improve the porosity of the catalyst. The result showed that a well-developed porous structure was observed, as the concentration of KOH increased activated biochar become more porous. 7M-KOH for chemical activation was the best condition to obtain a porous catalyst. It was found that the main factors affecting the FAME yield were dependent on various parameters including methanol: oil ratio, catalyst loading, reaction time and stirring speed via transesterification process. The highest yield of 94.06% was achieved on 0.5g of the catalyst activated by 7M-KOH, a methanol:oil ratio of 6:1 and a 1-hour reaction. The obtained biodiesel mainly composed of different fatty acid in follow order C18:1 > C16:0 > C18:2 > C18:0. Properties reached the ASTM D6751-12 and EN 14214:2012 standard, indicating that leucaena-derived biochar is potentially utilized in biodiesel production.